2001
DOI: 10.1037/0735-7036.115.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual-cycle synchrony: Problems and new directions for research.

Abstract: Since M. K. McClintock (1971) published the 1st study on menstrual synchrony among women, a number of other studies have also reported synchrony using a variety of methods. The most recent reports of synchrony come from A. Weller, L. Weller, and colleagues, and their findings of synchrony have been getting stronger (by their own account). In this article, the author analyzes their new methodology and presents 2 simulation studies that demonstrate how biases and errors can produce synchrony as an artifact. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 53 publications
3
54
0
Order By: Relevance
“…Such an effect was reported for humans (Stern and McClintock, 1998) and has been inferred in earlier studies reporting synchrony in humans (Weller and Weller, 1993). However, other studies or re-analysis of previous studies, have found no evidence of cycle synchrony in humans (Schank, 2001b; Strassmann, 1999; Whitten, 1999; Wilson, 1987, 1992), non-human primates (chimpanzee: (Matsumoto-Oda et al, 2007); Mandrill: (Setchell et al, 2011); macaque (Furtbauer et al, 2011)), rats (Schank, 2001a) or hamsters (Schank, 2000). It might be that cycle synchrony occurs only in very restricted and contextually-specific circumstances (McClintock, 2002) but, on balance, the evidence suggests that ovarian synchrony does not exist as a biologically meaningful phenomenon (Schank, 2001b, 2006).…”
Section: Ovulation Induction (Whitten Effect; (Whitten Et Al 1968))mentioning
confidence: 85%
“…Such an effect was reported for humans (Stern and McClintock, 1998) and has been inferred in earlier studies reporting synchrony in humans (Weller and Weller, 1993). However, other studies or re-analysis of previous studies, have found no evidence of cycle synchrony in humans (Schank, 2001b; Strassmann, 1999; Whitten, 1999; Wilson, 1987, 1992), non-human primates (chimpanzee: (Matsumoto-Oda et al, 2007); Mandrill: (Setchell et al, 2011); macaque (Furtbauer et al, 2011)), rats (Schank, 2001a) or hamsters (Schank, 2000). It might be that cycle synchrony occurs only in very restricted and contextually-specific circumstances (McClintock, 2002) but, on balance, the evidence suggests that ovarian synchrony does not exist as a biologically meaningful phenomenon (Schank, 2001b, 2006).…”
Section: Ovulation Induction (Whitten Effect; (Whitten Et Al 1968))mentioning
confidence: 85%
“…Menstrual cycle and hormonal birth control use have been noted to affect labial temperature, possibly through inconsistent habituation to repeated sexual stimuli (Slob et al, 1991). Although limited menstrual cycle and medication data were collected in this study, the information gathered was insufficient to adequately control or test the possible effects of either (Schank, 2001;Graham, 2002). Similarly, the effects of parity on genital sexual response are not well-characterized, and these data do not address potential variability due to childbirth experience.…”
Section: Discussionmentioning
confidence: 55%
“…284 However, supportive research has been criticized on methodological grounds, and the existence of this phenomenon remains controversial. 285 Also, while the vomeronasal organ-believed to be responsible for pheromone detection in animals-develops in utero in humans, it subsequently regresses and is largely believed to be nonfunctional in adults. 286 …”
Section: Pheromonesmentioning
confidence: 99%